Low levels of shade and climate change adaptation of Arabica coffee in southeastern Brazil. Issue 2 (February 2019) - Coltri, Priscila Pereira; Pinto, Hilton Silveira; Gonçalves, Renata Ribeiro do Valle; Zullo Junior, Jurandir; Dubreuil, Vincent
Abstract: Coffee is one of the most consumed beverages in the world, and its international market has been growing for many years. Unfortunately, the Brazilian coffee production is threatened by high temperatures projected by climate change models. We evaluated three schemes of low levels of shade, which avoid the loss of production, as a strategy to adapt coffee to possible climate change. Additionally, as field measurements are expensive and often difficult to implement, we used numerical simulation to complement the evaluation. The microclimate simulator software Envi-met is a computer program often used to simulate urban environments, and we tested it on agriculture design. We verified that the shaded schemes assessed in the field decreased the air temperature in 0.6 °C in the studied period and reduced other possible climate stressors such as wind speed, radiation and raised air humidity in the dry period. Envi-met described the studied meteorological variable cycle very well, showing that combining numerical modelling and field research may be an important tool for planning the adaptation of the coffee sector to possible climate change, allowing growers choose a proper technique for their regions and environmental conditions. Finally, we highlighted the importance of planning the shade scheme on coffee areas in an interdisciplinary approach, including local climate evaluation to achieve a balance between temperature attenuation and production.